2016
DOI: 10.22211/cejem/64998
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Polymorphic Transitions in Energetic Compounds

Abstract: Available data on the kinetics of polymorphic transitions (PTs) in energetic compounds under isothermal conditions are summarized and discussed. It is shown that the general kinetic regularities of these processes (stepwise and continuous regimes) depend on their topotactic mode (frontal or quasihomogeneous, respectively). In reverse PTs, a nucleation stage is not observed, which is explained by the presence of nuclei of the low-temperature polymorph in the preheated sample. The influence of mechanical effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[16][17][18] Chukanov and Zakharov have demonstrated that during crystallization of α-FOX-7 two types of crystals form: parallelepipeds formed by faces {100}, {010} and {001} and twinned crystals with characteristic re-entrant angles that have isometric shapes. [19] The authors assume that the presence of two crystals types in sample is the most likely reason for two-exponential law of β!α FOX-7 phase transition. According this research, the value of phase transition heat obtained by the DSC method under isothermal conditions is 22 J/g.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Chukanov and Zakharov have demonstrated that during crystallization of α-FOX-7 two types of crystals form: parallelepipeds formed by faces {100}, {010} and {001} and twinned crystals with characteristic re-entrant angles that have isometric shapes. [19] The authors assume that the presence of two crystals types in sample is the most likely reason for two-exponential law of β!α FOX-7 phase transition. According this research, the value of phase transition heat obtained by the DSC method under isothermal conditions is 22 J/g.…”
Section: Introductionmentioning
confidence: 99%